Iron-Dependent Regulation of MDM2 Influences p53 Activity and Hepatic Carcinogenesis - Dongiovanni, Paola (American Society for Investigative Pathology, 2010)
Iron overload is a risk factor for hepatocarcinoma, but the pathways involved are poorly characterized. Gene expression analysis in immortalized mouse hepatocytes exposed to iron or the iron chelator deferoxamine revealed that iron downregulated, whereas deferoxamine upregulated, mRNA levels of mouse double minute gene 2 (MDM2), the ubiquitin ligase involved in the degradation of the oncosuppressor p53. Regulation of MDM2 by iron status was observed at protein levels in mouse hepatocytes and rat liver, and was associated with specular changes in p53 expression. Iron dependent regulation of MDM2/p53 was confirmed ex-vivo in human monocytes, by manipulation of iron pool and in a genetic model of iron deficiency, leading to modulation of p53 target genes involved in the antioxidant response and apoptosis. Iron status influenced p53 ubiquitination and degradation rate, and the MDM2 inhibitor nutlin increased p53 levels in iron-depleted cells. Furthermore, nutlin enhanced the antiproliferative activity of deferoxamine in HepG2 hepatoblastoma cells. The MDM2 −309T > G promoter polymorphism, determining increased MDM2 and lower p53 activity, was associated with higher risk of hepatocarcinoma in cirrhotic patients with hemochromatosis, and with HFE mutations in patients with hepatocarcinoma without hemochromatosis, suggesting an interaction between MDM2 and iron in the pathogenesis of hepatocarcinoma. In conclusion, iron status influences p53 activity and antioxidant response by modulating MDM2 expression. MDM2 inhibitors may enhance the antiproliferative activity of iron chelators.